2019
DOI: 10.17508/cjfst.2019.11.1.14
|View full text |Cite
|
Sign up to set email alerts
|

Influence of drying temperature and pretreatment on the drying characteristics and quality of dried cashew (Anacardium occidentale L.) apple slices

Abstract: This study evaluated the mineral content, browning extent, proximate content, the sensory analysis in the yellow variety of cashew apple slices, for both fresh and after being subjected to pretreatment, at three different drying temperatures. Fresh cashews were harvested, sliced into 7 mm thickness, pretreated by dipping the slices into ascorbic acid and dried at the temperature of 45 °C, 55 °C and 65 °C using the hot air convective dryer at a constant air velocity of 0.8 m/s. During the drying the weight loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 11 publications
1
4
0
Order By: Relevance
“…For those reasons, 6 mm was selected for processing in the next stage. This result is also similar to the study of Olalusi & Erinle (2019) on Anacardium Occidentale L. in Nigeria, which showed that cashew apples were sliced at 7 mm before acid pretreatment and dried at 55°C, the tannin content decreased with a large value from 2.2028 g compared to 261.3 g in fresh samples, and other contents such as vitamin C and calcium obtained good values. Vitamin C is the main ingredient in cashew apple, as reported by Lagnika et al.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For those reasons, 6 mm was selected for processing in the next stage. This result is also similar to the study of Olalusi & Erinle (2019) on Anacardium Occidentale L. in Nigeria, which showed that cashew apples were sliced at 7 mm before acid pretreatment and dried at 55°C, the tannin content decreased with a large value from 2.2028 g compared to 261.3 g in fresh samples, and other contents such as vitamin C and calcium obtained good values. Vitamin C is the main ingredient in cashew apple, as reported by Lagnika et al.…”
Section: Resultssupporting
confidence: 90%
“…In addition, the average drying time is about 268 min to achieve the desired moisture level (12%–13%). Previous studies (Olalusi & Erinle, 2019) also mentioned the use of a temperature of 55°C for the drying process of cashew apples. At this temperature, the loss of vitamin C can be reduced, the browning effect is less, and the loss of tannin is high.…”
Section: Resultsmentioning
confidence: 99%
“…The moisture analyzer (MB120, Ohaus, USA) was used to assist in determining the moisture content of fruit bars and fresh mango [ 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cashew is one of the domestically focused crops upon which the Nigerian government is currently seeking to engender food security and build a healthy base for agricultural export, thereby leading to economic development. Despite this and its being rich in vitamins and minerals, which are good for health, cashew apple is still not exploited to its full potential by developing new products in Nigeria, unlike other countries fruit (Olalusi and Erinle, 2019). Also, it is inaccessible to poor local consumers which may be due to poor harvest practices, among others.…”
Section: Machine For Fruit Harvestingmentioning
confidence: 99%